Designing and Manufacturing a Portable Rainfall Simulator - sima Mohammadi; Arian Amini; Amin Salesi; Mohammadreza Ahmadi; Mostafa Badiei; Mahbobe Jalali (Environmental Resources Research, 2022)
Rain simulation is a method widely used in detecting hydrological and erosional processes. Most portable samples have inconvenient and challenging transport, high water consumption, and energy supply. The objective of this study was to design and test a rainfall simulator characterized by the following innovative features: 1) The simulator is easy to be transported and assembled in the field, thereby allowing the necessary experimental replicates, 2) Applicability on different slopes. The first calibration step regarded the spatial distribution of rainfall, the stability of the rainfall intensity, and the reproducibility of the rainfall intensities over time (among successive experiments). Next, the drop size distribution (DSD) and the related rainfall characteristics (median volumetric drop diameter D50 and mean kinetic energy per unit area and unit depth) were evaluated by the flour pellet method. A fluorescent tracer method is used to measure the velocity of falling drops. According to the findings, the Christiansen uniformity coefficient (Cu) of this rainfall simulator varies from 77-87% for rainfall intensities of 35-75 mmh-1. The best rainfall distribution has been achieved for rainfall intensities of 55 and 75 mmh-1, with rain droplet sizes ranging from 0.6 to 3.8 mm. The raindrop velocity was also measured by photo-shooting and revealed a velocity rate of 2.7-5.7 ms-1. The system allows rainfall simulation on the fields and under laboratory conditions. Moreover, erosion, runoff, and sediment production under natural and intact soil conditions can also be examined with the highest possible accuracy